Red Cell Properties after Different Modes of Blood Transportation - Makhro, Asya; Huisjes, Rick; Verhagen, Liesbeth P.; Mañú-Pereira, María del Mar; Llaudet-Planas, Esther; Petkova-Kirova, Polina; Wang, Jue; Eichler, Hermann; Bogdanova, Anna; van Wijk, Richard; Vives-Corrons, Joan-Lluís; Kaestner, Lars (Frontiers in Physiology, 2016)
Transportation of blood samples is unavoidable for assessment of specific parameters in blood of patients with rare anemias, blood doping testing or for research purposes. Despite the awareness that shipment may substantially alter multiple parameters, no study of that extend has been performed to assess these changes and optimize shipment conditions to reduce transportation-related artifacts. Here we investigate the changes in multiple parameters in blood of healthy donors over 72 hours of simulated shipment conditions. Three different anticoagulants (K3EDTA, Sodium Heparin and citrate-based CPDA) for two temperatures (4oC and room temperature) were tested to define the optimal transportation conditions. Parameters measured cover common cytology and biochemistry parameters (complete blood count, hematocrit, morphological examination), red blood cell (RBC) volume, ion content and density, membrane properties and stability (hemolysis, osmotic fragility, membrane heat stability, patch-clamp investigations and formation of micro vesicles), Ca2+ handling, RBC metabolism, activity of numerous enzymes and O2 transport capacity. Our findings indicate that individual sets of parameter may require different shipment settings (anticoagulants, temperature). Most of the parameters except for ion (Na+, K+, Ca2+) handling and, possibly, reticulocytes counts, tend to favor transportation at 4oC. Whereas plasma and intraerythrocytic Ca2+ cannot be accurately measured in the presence of chelators such as citrate and EDTA, majority of Ca2+-dependent parameters are stabilized in CPDA samples. Even in blood samples from healthy donors transported using optimized shipment protocol the majority of parameters were stable within 24 hours, the condition that may not hold for the samples of patients with rare anemias. This implies for the as short as possible shipping using fast courier services to the closest expert laboratory at reach. Mobile laboratories or the travel of the patients to the specialized laboratories may be the only option for some groups of patients with highly unstable RBCs.